PENGARUH PARTISIPASI SISWA DALAM KOPERASI SEKOLAH DAN HASIL BELAJAR MATA PELAJARAN EKONOMI BAB KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA SISWA KELAS XI IIS SMA NEGERI 2 MALANG TAHUN AJARAN 2014/ 2015 - Lia Ernes Pauli; Lisa Rokhmani; Achmad Ali Wafa (Jurnal Pendidikan Ekonomi, 2015)
Interest in entrepreneurship is a desire and a sense of interest to entrepreneurs. Entrepreneurship interest identified in keinginann to be a good entrepreneur and trying to develop the ability to look and see business opportunities, gather the resources needed to make something more useful and can take keuntunngan. Interest in entrepreneurship in students can be nurtured and developed at school through the learning economy, besides one of them also through the facilities provided by the school as a place of business or a business that is in school, the school cooperative. This study aims to explain the influence of the independent variable is participation in the cooperative school students and student learning outcomes on economic subjects and entrepreneurship chapter dependent variable is the students' interest in entrepreneurship either partially or simultaneously. This study uses a quantitative approach with a kind of explanatory research and the sample amounted to 88 students drawn from the primary data source and using the questionnaire technique. The results using multiple linear regression analysis with SPSS 16.00 for Windows indicates that the data are normally distributed, besides the independent variable has a positive and significant effect on the dependent variable the percentage coefficient of determination of 66.6%.